Unlocking the potential of sepiolite: Designing high-performance energy storage materials - Yanhuai Ding; Yizhi Jiang; Dongzhao Jin; Yunhong Jiang; Ana C.S. Alcântara (Energy Reviews)
Sepiolite, with its unique microporous structure, high specific surface area, excellent thermal stability, and chemical stability, has significant potential for application in the field of energy storage. However, a systematic summary of its application in key components of secondary batteries, such as electrodes, separators, and solid electrolytes, is lacking. This review aims to provide a comprehensive overview of the applications of natural fibrous magnesium silicate mineral-sepiolite and its composites in energy storage and conversion, focusing particularly on lithium-ion batteries (LIBs), lithium-sulfur batteries (LSBs), zinc-ion batteries (ZIBs), and fuel cells. We have reviewed various preparation methods for sepiolite-based composite materials and discussed their applications in the field of energy storage. This review particularly emphasizes the impact of structural regulation on the electrochemical performance of sepiolite and explores the process requirements for the large-scale fabrication of sepiolite composite materials. Our work indicates that sepiolite itself possesses certain energy storage capabilities, and the preparation of composite nanomaterials through solid-phase methods can significantly enhance the electrochemical performance of sepiolite. By utilizing sepiolite's morphological and structural characteristics, the composite materials not only inherit the form of sepiolite but also achieve a significant enhancement in electrochemical performance. Nevertheless, the regulatory mechanism of sepiolite's electrochemical performance is not yet fully understood, which points the way for future research. Future studies should focus on the structural regulation of sepiolite and the development of large-scale preparation processes, in order to widely apply it in high-performance energy storage systems.